Rate of testicular histology failure in predicting successful testicular sperm extraction - Castellano, Stefano; Tondo, Francesca; Bulbul, Ozgur; Aprea, Sabrina; Monti, Emanuela; Carnesi, Edoardo; Levi Setti, Paolo Emanuele; Albani, Elena (Frontiers in Endocrinology, 2024)
This is a retrospective analysis of 526 TESE patients. We compared our evaluations, in terms of retrieved sperm concentration and number of cryopreserved paillettes for any patients, with testicular histology reports. This way we tried to gain a better understanding of the different criteria used by the two laboratory techniques. After the extraction of the testis, the resulting sample was immediately given to the embryologist, who examined the tubules for sperm cryopreservation. During the same procedure, a different specimen was destined to the histological analysis. The comparison between the two methodological approaches was carried out through a score. Concordance between TESE and testicular histology outcomes was found in 70,7% of patients; discordance was found in 29,3% of patients. Among the discordance outcomes, in approximately 95% we found at least 1 sperm in the TESE retrieval, while the histology report did not find any spermatozoa or found not enough compared to our evaluation; in only 5% of cases we did not find any spermatozoa or found not enough compared to what was detected in the testicular histology. The main limitation of this study lies in the techniques used to achieve the results. Sperm cryopreservation gives quantitative results, in terms of sperm concentration and number of cryopreserved paillettes; on the other hand, the histopathology report is based on a qualitative examination. Based on our experience, to increase diagnostic accuracy, a larger biopsy should be sent to the histopathology laboratory; another option may be to use TESE cell suspension (the same embryologists employ for cryopreservation) for cytological evaluation of spermatogenesis.